A renal-clearable duplex optical reporter for real-time imaging of contrast-induced acute kidney injury - Huang, Jiaguo (2020)
Despite its high morbidity and mortality, contrast‐induced acute kidney injury (CIAKI) remains a diagnostic dilemma because it relies on in vitro detection of insensitive late‐stage blood and urinary biomarkers. We report the synthesis of an activatable duplex reporter (ADR) for real‐time in vivo imaging of CIAKI. ADR is equipped with chemiluminescence and near‐infrared fluorescence (NIRF) signaling channels that can be activated by oxidative stress (superoxide anion, O2.−) and lysosomal damage (N‐acetyl‐β‐d‐glucosaminidase, NAG), respectively. By virtue of its high renal clearance efficiency (80 % injected doses after 24 h injection), ADR detects sequential upregulation of O2.− and NAG in the kidneys of living mice prior to a significant decrease in glomerular filtration rate (GFR) and tissue damage in the course of CIAKI. ADR outperforms the typical clinical assays and detects CIAKI at least 8 h (NIRF) and up to 16 h (chemiluminescence) earlier.